(untitled) (Research, Society and Development, 2022)
This article aims to analyze the role of design and education as cultural mediation in the preservation of Brazilian heritage. It is a study with a qualitative approach of the bibliographic and descriptive type, dialogues with the interface of knowledge of design, education, mediation and demonstrates its relationship with the preservation of national cultural heritage. It presents the following guidelines: Venice Charter, 1964; Restoration Letter, 1972; and Carta de Burra, 1980, to exemplify the scope of international preservation applied to Brazil. Vieira Pinto, Laraia, Hall and Freire were the basis for this study, as well dissertations from the CAPES database. This focus made it possible to place the research within the scope of the scientific needs of the reality of design and education. The study was guided by the following questions, “How can design contribute to the appreciation of cultural heritage?” and “What is the relationship between design and heritage education as cultural mediation?”. Thus, heritage charters linked to Institute of National Historic and Artistic Heritage (IPHAN) were analyzed to identify preservation guidelines that can be applied to the Brazilian political and cultural context. In addition, there was a dialogue with the fundamentals of design and education related to mediation, valuing and preserving culture, historicity and heritage. It was concluded that by combining design with education as a cultural mediation, the discourse of preservation of national identity is fostered through the real need for research, social awareness and public policies, so that there is a projectual creation of value in the cultural educational process, for both mediate being and being in the world.